Bahasa Sanskerta dan Bahasa Melayu - Collins, James T., 1946- (Jakarta : Kepustakaan Populer Gramedia, 2009)
History and development of Sanskrit and Malay languages and their usage in Indonesia
Includes bibliographical references (p. [127]-140)
Keywords: Sanskrit language -- History; Malay language -- History